Influence of Brand on Customer Behaviour in Mobile Phone Choice: Comparison between China and The UK - Yang, Mingyi (2014)
Brand has been seen as a powerful tool to attract customers’ attention even sometimes changes their purchasing decision. Aaker (1991) points out brand can be regarded as equity and mainly involves four elements (brand loyalty, brand association, brand awareness and perceived quality) that add extra value to the products. This thesis explores that those factors how to influence customer purchasing choice in mobile phone market, while combing several factors which generally influence customer mobile phone choice. In addition to compare the different influences in China and in the UK. Finally, this study finds out which factor is the most influential factor among four key factors respectively in China and in the UK. 136 Self-complete questionnaires have been used to run SPSS software in order to do statistic analysis. The findings recommended that Chinese marketers should keep developing brand benefit, and the British marketers should focus on customers’ interests and the actual needs. It is important that perceived quality should cause the attention of markers and manufactures both in China and in the UK.